Exploring creativity through artists’ reflections - Daniel, Ryan (Creativity Studies, 2021)
The concept of creativity has been theorized and debated for millennia, dating back to the Greek philosopher Plato, who referred to “divine madness” in poets. Debates continue as to whether creativity is a gift or talent, a product of the genius gene, a side effect of mental health conditions, or if it is learned and nurtured through the environments and societies in which an individual grows and develops. While there is a wealth of research that sets out to define the concept of creativity, and numerous theoretical models have emerged since the early part of the 20th century, little of that involves artists reflecting on the concept. In order to explore this area, this study surveyed 314 artists from a range of countries, using an online survey, which invited them to reflect on creativity as a concept and how they understand it within their artistic practice. The findings reveal that creativity is a complex term and there is a range of understandings demonstrated by those who practice art-making. Questions for key stakeholders in education and policy are also raised, in terms of the role and place of artistic creativity in society.